Pemberdayaan Masyarakat Melalui Pemanfaatan Limbah Organik Rumah Tangga Menjadi Pupuk Organik Cair (POC) di Komplek Perumahan Royal Residence 2 - Destian Destian; Masrohatus Shalikhah; Noni Mareta; Reydina Putri; Intan Cahaya; Tirta Toba; Rezza Pahlevi; Khosi’in Khosi’in (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Household organic waste, such as sisa sayuran and kulit buah, is a type of rubbish that is frequently produced by the community but is not always handled optimally. The goal of this community engagement program is to increase locals' awareness and proficiency in using the limbah organik rumah tangga as a POC in Komplek Perumahan Royal Residence 2. The methods that are used include socialization, persiapan, and POC demonstration. Top of vegetable scraps, fruit peels, EM4, brown sugar, rice washing water, and air are among the tools used. The fermentation process is carried out over the course of 14 days, with regular pengadukan every day. The results of the activity indicate that the public has a better understanding of organic waste and is capable of practicing POC production on their own. In addition to producing organic liquid that can be used for garden plants and family medicinal plants (TOGA), this activity also increases public awareness of the importance of waste that is environmentally friendly. Accordingly, using household organic waste as POC can be an alternative to waste management in the residential environment.